Computer-Based Simulation on LCB Positions in Indonesian Traditional Wooden Ship - Luthfi Abdurrahman; Andi Mursid Nugraha Arifuddin; Andi Ardianti; Hariyono; Musa Lolo; Reynadi Firzy Irawan; Pria Adi Pengestu; Dimas Prayoga; Aldo Pangestu; Muhammad Uswah Pawara (International Journal of Marine Engineering Innovation and Research, 2024)
A Traditionl Wooden ship in North Penajam Paser is built without initial calculation to predict the resistance that will occur based on the shape of the hull. The ship is built solely based on the main dimensions and the number of engines to be installed, without considering the optimal hull shape. The hull shape is an important component in supporting the hydrostatic performance of a ship. Planning the hull's shape affect the ship's resistance value and ultimately impacts the ship's engine power requirements. The purpose of this research is to obtain the resistance value of the existing ship and determine the hull shape with a lower resistance value through computer-based simulations. The computer simulation approach based Holtrop method is used to determine the position of the LCB point based on the hull shape. Then, it examine the effect of the LCB position on the ship’s resistance of the hull shape. The hull shape simulation was conducted without changing the ship’s main dimensions. The simulation result show that the position of the LCB on the existing hull shape is 8.514 m from the AP, with a ship resistance value is 7.4 kN. Meanwhile, the optimum hull shape was found when the location of the LCB point was moved 0.1 m forward from its initial position (model 4). The resistance value in Model 4 decreased by 3.8% compared to the initial resistance value. In addition to model 4, models 2 and 3 also reduced the ship's resistance value, with changes of 0.9% and 2.1%, respectively. Furthermore, this optimal hull shape can be developed in the next analysis stage, such as ship structure planning and other design analyses.